Answer:
C. x=33/10 , y=-3/5, z=1/10.
Explanation:
6x+15y+12z=12 (A)
3x-9y-3z=15 (B)
3x+12y+3z=3 (C)
Subtract B - C to eliminate the term in x:
-21y - 6z = 12 (D) Now multiply B by 2:
6x - 18y - 6z = 30 (E) A - E will eliminate x:
33y + 18z = -18 (F)
Now solve equations (D) and (F):
-21y - 6z = 12 Multiply this by 3:
-63y - 18z = 36 (G)
G + F will eliminate z:
-30y = 18
y = -18/30 = -3/5.
So substituting for y
-21(-3/5) - 6z = 12
-6z = 12 - 63/5 = -3/5
z = 1/10
Finally we substitute the values of y and z in equation A to find x:
6x+15(-3/5)+12(1/10)=12
6x - 9 + 1.2 = 12
6x = 19.8
x = 3.3 = 33/10.